PREPARATION OF PVC HOLLOW FIBER MEMBRANE USING (DMAC/ACETONE) - M. Hussein, Fawziea; S. Merzah, Amel; Rashad, Zaid Waadulla (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Membrane manufacturing system was operated using dry/wet phase inversion process. A sample of hollow fiber membrane was prepared using (17% wt PVC) polyvinyl chloride as membrane material and N, N Dimethylacetamide (DMAC) as solvent in the first run and the second run was made using (DMAC/Acetone) of ratio 3.4 w/w. Scanning electron microscope (SEM) was used to predict the structure and dimensions of hollow fiber membranes prepared. The ultrafiltration experiments were performed using soluble polymeric solute poly ethylene glycol (PEG) of molecular weight (20000 Dalton) 800 ppm solution 25 °C temperature and 1 bar pressure. The experimental results show that pure water permeation increased from 25.7 to 32.2 (L/m2.h.bar) by adding acetone to the dope solution, while rejection decreased from 91.8 to 63.2%.